Optimizing Village Accountability Through SISKEUDES Financial System Implementation - Anggraeni, Marita; Fitriyah , Hadiah (Indonesian Journal of Public Policy Review, 2024)
Law no. 6 of 2014 mandates village government accountability, leading to the creation of the Village Financial System (SISKEUDES) by BPKP. This study investigates SISKEUDES implementation in Kepunten Tulangan Sidoarjo Village, focusing on APBDes (Village Budget) accountability. Using qualitative methods, including observation, interviews, and documentation, data were collected from key informants. Findings reveal SISKEUDES significantly enhances accountability and transparency, aiding efficient financial management and timely reporting. This research underscores the importance of technological solutions in improving local governance and promoting transparency. Highlight: echnology Boosts Accountability: SISKEUDES enhances village government financial transparency. Research Methods: Employed qualitative techniques including observation and interviews. Governance Efficiency: SISKEUDES facilitates efficient financial management and transparency. Keywoard: SISKEUDES, Accountability, Transparency, Local Governance, Financial Management